Interrelation between miRNAs Expression Associated with Redox State Fluctuations, Immune and Inflammatory Response Activation, and Neonatal Outcomes in Complicated Pregnancy, Accompanied by Placental Insufficiency - Vladislava A. Gusar; Angelika V. Timofeeva; Vitaliy V. Chagovets; Mikhail Yu. Vysokikh; Nataliya E. Kan; Ludmila A. Manukhova; Maria V. Marey; Gennadiy T. Sukhikh (MDPI AG, 2022)
Redox disbalance in placental cells leads to the hyperproduction of reactive oxygen species (ROS), it mediates the dysregulation of the maternal immune tolerance to a semi-allogenic fetus, inducing pro-inflammatory reactions, and it plays a central role in perinatal complications and neonatal disease programming. Microvesicles, which provide transplacental communication between a mother and fetus, contain microRNAs (miRNAs) that are sensitive to oxidative stress (OS) mediators and can control the balance of ROS production and utilization in target cells. In the context of this paradigm, we evaluated the markers of redox balance-MDA and 4-HNE for OS and GPx, and SOD, CAT, and GSH for the antioxidant system in the cord blood plasma of newborns diagnosed with fetal growth restriction (FGR)-by using polarography, spectrophotometry, and Western blotting. The expression of miRNAs associated with OS, immune and inflammatory responses in the blood plasma of newborns with intrauterine pneumonia (IP), neonatal sepsis (NS) and respiratory distress syndrome (RDS) was evaluated by a quantitative RT-PCR. Significant differences in the MDA level and reduced GPx and CAT activity were co-found for early-onset FGR (i.e., <34 gestational age). Significant correlations were found with a low birth weight by Apgar scores with reduced levels of antioxidant enzymes. Indeed, the level of OS markers increased in early-onset FGR in newborns with an extremely low body weight and high echogenicity of the periventricular zones, and reduced in late-onset FGR in newborns with IP, hyperbilirubinemia, intraventricular hemorrhage (IVH) and cerebral cysts. A prognostic model (AUC = 1; cutoff-0.5) was developed to assess the risk of IVH in newborns diagnosed with FGR based on the assessment of the OS markers (i.e., MDA + 4 HNE + CAT + GSH). A significant increase in the miR-127-3p expression was found in the plasma of newborns with NS (<32 GA; p ≤ 0.03 and >32 GA; p ≤ 0.009), IP (>32 GA; p ≤ 0.0001), and RDS (>32 GA; p ≤ 0.03). At the same time, the expression of miR-25-3p (p ≤ 0.03) was increased only in newborns with NS (>32 GA; p ≤ 0.03). The risk of developing IVH for premature newborns with IP (AUC = 0.8; cutoff-0.6) and NS (AUC = 0.68; cutoff-0.49) was assessed based on the miR-25-3p and miR-127-3p expression. Several key transcription factors were identified as the targets of studied miRNA since they are involved in the regulation of OS (NRF2), signaling and activation of the immune response (PRDM1, CCL26) and, also, inflammatory responses (NFKB1). The study of these miRNAs showed that they are involved in the modulation of processes leading to perinatal complications. Moreover, miR-127-3p is related to pro-inflammatory reactions and the formation of the macrophage phenotype in newborns with IP, NS, and RDS, while miR-25-3p is associated with an inhibition of macrophage migration and activation of antioxidant enzymes, which may prevent the development of oxidative damage in newborns with NS.